Development of Low Frequency High Temperature Ultrasonic Transducers for In-service Monitoring of Pipework in Power Plants. (2016) - Dhutti, A.; Tumin, S.A.; Mohimi, A.; Kostan, M.; Gan, T.H.; Balachandran, W.; Selcuk, C.
Abstract: In this paper, a low-frequency (20-100 kHz) long-range ultrasonic guided wave transducer for in-service structural health monitoring of high temperature pipework in power plants has been developed. The transducer is designed for continuous operation at a target temperature of 350 °C. This paper describes the methodology followed to develop and test the high temperature transducer. The method includes selection of the suitable piezoelectric material and characterisation of their high temperature properties for the desired thickness-shear mode of vibration to validate its performance at the target temperature. The assembly procedure established for manufacturing transducer is discussed. Ultrasonic performance of the developed transducer was examined and has demonstrated its application for in-service monitoring of pipework operating at the target temperature.